Work-related cancer in Brazil: description of the notifications, 2007-2012 - Santos Carneiro e Cordeiro, Tecia Maria; Carneiro Neto, Jose Nunes [UNESP]; Santana Mattos, Amalia Ivine; Souza, Fernanda de Oliveira; das Merces, Magno Conceicao; Santana, Thiago da Silva (Centro Univ Sao Camilo, 2017)
It is estimated that 2-4% of the world's cancer is associated with exposure to carcinogens in the workplace. The objectives of the study were to describe the characteristics of occupational cancer notifications in Brazil from 2007 to 2012, and to evaluate the completeness of the variables of these notifications. This was a descriptive cross-sectional study from the data collected in the Injury Notification Information System. In the study period 269 cases of occupational cancer were more often reported in the Midwest (59.1%), of cases of skin cancer (92.0%), among workers in agriculture, forestry and hunting and fishing (43.5%), who were 11-20 years of work in profession (24.2%), and were self-employed (30.1%). As for classification of incomplete fields, it was evident that the minority of the variables in the notification were poorly filled out. The complete filling out of notifications and monitoring workers' health with preventative actions against occupational cancers are necessary to reduce their incidence and promote workers' health in healthy environments.
Keywords: Epidemiology; Descriptive; Neoplasms; Occupational Health; Disease Notification